Exploring the Role of Islamic Counselors in Premarital Stunting Prevention in Depok City, Indonesia: A Qualitative Descriptive Study Informed by the Theory of Planned Behavior - Erik Ekowati; Evi Martha; Sutanto Pryo Hastono; Nana Mulyana; Nina Herlina; Arifah Alfiyyah; Tri Auri Putri Ayuningtyas (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Islamic counsellors occupy a strategic position in premarital services and are increasingly expected to support stunting prevention by delivering early health and nutrition messages to prospective couples. However, their involvement remains constrained by limited training, time, resources, and coordination with health services. Methods: This qualitative descriptive study explores the role of Islamic counsellors in stunting prevention for prospective couples using the Theory of Planned Behavior (TPB) as an analytical framework. In-depth interviews were conducted with 21 participants comprising 10 Islamic counsellors at the Office of Religious Affairs (KUA), 6 prospective couples, and 5 health workers in Depok City, West Java. Participants were selected through purposive sampling to capture diverse stakeholder perspectives across institutional roles and geographic sub-districts. Data were analysed using a hybrid deductive-inductive thematic approach informed by the TPB constructs of attitudes, subjective norms, and perceived behavioral control. Data saturation was reached after 18 interviews, with three additional confirmatory interviews conducted. Results: Three principal themes emerged: (1) religious and moral responsibility as behavioral beliefs shaping counselors’ positive attitudes toward integrating stunting prevention, consistent with the attitudinal component of TPB; (2) community trust and institutional expectations as normative influences reinforcing supportive subjective norms; and (3) training, time, and resource constraints affecting counselors’ perceived behavioral control, which moderates their intentions and counseling practices. These themes demonstrate how TPB constructs explain the mechanisms through which Islamic counselors navigate their health communication role within structural limitations. Conclusion: Islamic counsellors hold perceived potential to contribute to upstream stunting prevention through premarital counselling, though this potential is conditioned by structural constraints including limited training, restricted counseling duration, and variable institutional coordination. These findings represent perceptions and implementation experiences rather than demonstrated impact on stunting outcomes. Strengthening structured training, standardized premarital counselling modules, and sustained cross-sector collaboration between religious and health sectors is recommended to support counselors’ capacity. Further research employing mixed-methods designs with outcome measurement is needed to evaluate the effectiveness and generalizability of these findings.